HIV-associated intussusception. Issue 8 (13th August 2021) - Mewaldt, Christian; Mehta, Raaj
ABSTRACT: A 39-year-old man with untreated HIV presented with watery, non-bloody diarrhea and associated 25-lb weight loss. His workup was notable for a CT abdomen/pelvis which showed an entero-enteric intussusception of 3.4 cm without an underlying pathologic mass. The patient's intussusception resolved without intervention, as is typical of telescoping <3.5 cm. HIV is associated with an increased risk of developing intussusception because of an increased incidence of infectious and neoplastic conditions of the bowel.